Bachelor of Social Sciences with Honours (Social Work Studies) - Universiti Malaysia Sarawak, Faculty of Social Sciences & Humanities (Universiti Malaysia Sarawak (UNIMAS), 2022)
Sijil Sarjana Muda Fakulti Sains Sosial dan Kemanusiaan 2022 bagi 73 orang pelajar.